The Effect of Copper on Endometrial Receptivity and Induction of Apoptosis on Decidualized Human Endometrial Stromal Cells. (July 2018) - Carrascosa, Jose P.; Cotán, David; Jurado, Inmaculada; Oropesa-Ávila, Manuel; Sánchez-Martín, Pascual; Savaris, Ricardo F.; Tan, Justin; Sánchez-Alcázar, Jose A.; Tan, Seang L.; Horcajadas, José Antonio
Intrauterine devices (IUDs) have been widely used to prevent pregnancies with great efficacy during decades. It has been demonstrated that IUD alters the endometrial gene expression, but there is no scientific data about how copper, a metal commonly used in these devices, by itself, is able to influence the processes of endometrial receptivity and apoptosis in decidualized human endometrial stromal cells. Five endometrial samples were obtained from fertile women and processed by a standard protocol to obtain human endometrial stromal cells for in vitro studies. Stromal cells were cultured in vitro and decidualized for 8 days. At day 6, copper was added to the treatment group or camptothecin as positive control for apoptosis until day 8. Five endometrial samples were used in each group. The aim of this study was to analyze the effect of copper in apoptosis and necrosis by flow cytometry, to visualize the apoptotic microtubule network during apoptosis by immunofluorescence, and finally to determine the gene expression profile of a panel of 192 genes related to endometrial receptivity and immune system by quantitative reverse transcription PCR (RT-qPCR). Copper, compared to the decidualized group, induced changes in the gene expression by an order of magnitude in 49 genes (42 up- and 9 downregulated). This alteration in the decidualization gene signature by copper includes 19 genes involved in the endometriosis pathology and others related to other gynecological disorders such as preeclampsia and infertility. Our results indicate that copper does not increase the apoptosis level induced by the decidualization treatment. However, copper alters the gene expression of some biomarkers of endometrial receptivity and immune response.